PRIMVAC vaccine adjuvanted with Alhydrogel or GLA-SE to prevent placental malaria: a first-in-human, randomised, double-blind, placebo-controlled study - Sirima, Sodiomon; Havelange, Nicolas; Leroy, Odile; Viebig, Nicola (The lancet. Infectious diseases, 2020)
Background - PRIMVAC is a VAR2CSA-derived placental malaria vaccine candidate aiming to prevent serious clinical outcomes of Plasmodium falciparum infection during pregnancy. We assessed the safety and immunogenicity of PRIMVAC adjuvanted with Alhydrogel or glucopyranosyl lipid adjuvant in stable emulsion (GLA-SE) in French and Burkinabe women who were not pregnant. - Methods - This first-in-human, randomised, double-blind, placebo-controlled, dose escalation trial was done in two staggered phases, a phase 1A trial in 18-35-year-old women who were malaria naive in a hospital in France and a subsequent phase 1B trial in women who were naturally exposed to P falciparum and nulligravid in the clinical site of a research centre in Burkina Faso. Volunteers were recruited into four sequential cohorts receiving PRIMVAC intramuscularly at day 0, 28, and 56: two cohorts in France receiving 20 μg or 50 μg of PRIMVAC and then two in Burkina Faso receiving 50 μg or 100 μg of PRIMVAC. Volunteers were randomly assigned (1:1) to two groups (PRIMVAC adjuvanted with either Alhydrogel or GLA-SE) in France and randomly assigned (2:2:1) to three groups (PRIMVAC adjuvanted with either Alhydrogel, GLA-SE, or placebo) in Burkina Faso. Randomisation was centralised, using stratification by cohort and blocks of variable size, and syringes were masked by opaque labels. The primary endpoint was the proportion of participants with any grade 3 or higher adverse reaction to vaccination up until day 35. Safety at later time points as well as humoral and cellular immunogenicity were assessed in secondary endpoints. This trial is registered with ClinicalTrials.gov, NCT02658253. - Findings - Between April 19, 2016, and July 13, 2017, 68 women (18 in France, 50 in Burkina Faso) of 101 assessed for eligibility were included. No serious adverse event related to the vaccine occurred. PRIMVAC antibody titres increased with each dose and seroconversion was observed in all women vaccinated with PRIMVAC (n=57). PRIMVAC antibody titres reached a peak (geometric mean 11 843·0, optical density [OD] 1·0, 95% CI 7559·8-18 552·9 with 100 μg dose and GLA-SE) 1 week after the third vaccination (day 63). Compared with Alhydrogel, GLA-SE tended to improve the PRIMVAC antibody response (geometric mean 2163·5, OD 1·0, 95% CI 1315·7-3557·7 with 100 μg dose and Alhydrogel at day 63). 1 year after the last vaccination, 20 (71%) of 28 women who were vaccinated with PRIMVAC/Alhydrogel and 26 (93%) of 28 women who were vaccinated with PRIMVAC/GLA-SE still had anti-PRIMVAC antibodies, although antibody magnitude was markedly lower (452·4, OD 1·0, 95% CI 321·8-636·1 with 100 μg dose and GLA-SE). These antibodies reacted with native homologous VAR2CSA expressed by NF54-CSA infected erythrocytes (fold change from baseline at day 63 with 100 μg dose and GLA-SE: 10·74, 95% CI 8·36-13·79). Limited cross-recognition, restricted to sera collected from women that received the 100 μg PRIMVAC dose, was observed against heterologous VAR2CSA variants expressed by FCR3-CSA (fold change from baseline at day 63: 1·49, 95% CI 1·19-1·88) and 7G8-CSA infected erythrocytes (1·2, 1·08-1·34). - Interpretation - PRIMVAC adjuvanted with Alhydrogel or GLA-SE had an acceptable safety profile, was immunogenic, and induced functional antibodies reacting with the homologous VAR2CSA variant expressed by NF54-CSA infected erythrocytes. Cross-reactivity against heterologous VAR2CSA variants was limited and only observed in the higher dose group. An alternate schedule of immunisation, antigen dose, and combinations with other VAR2CSA-based vaccines are envisaged to improve the cross-reactivity against heterologous VAR2CSA variants. - Funding - Bundesministerium für Bildung und Forschung, through Kreditanstalt für Wiederaufbau, Germany; Inserm, and Institut National de Transfusion Sanguine, France; Irish Aid, Department of Foreign Affairs and Trade, Ireland.
Gesehen am 17.06.2020